Effect of structured nurse-patient conversation on preventing falls among patients in an acute care hospital: A mixed study - Kathrin Weber; Susanne Knueppel Lauener; Mieke Deschodt; Florian Grossmann; René Schwendimann (Elsevier, 2024)
Objectives: Inpatient falls are a major patient safety issue in acute care hospitals. Multifactorial in-hospital fall prevention programs have shown reductions in falls and related risks. One common element of successful programs is active patient involvement. This study objective was to explore patients' and nurses' experiences with a structured intervention to foster patient involvement. Methods: This study was conducted between September 2020 and April 2021 in a university hospital neurological ward. The studied intervention consisted of a falls information leaflet, and a structured nurse-patient conversation about fall risk-reduction activities. Nurses were trained to deliver the intervention and supported throughout the study. Nurses' and patients' experiences regarding personal involvement, satisfaction, and confidence were surveyed and analyzed quantitatively and qualitatively. Results: Fifty-six patients recruited by ward nurses received the intervention. After receiving the intervention, patients reported high levels of satisfaction with the in-hospital fall prevention conversation. Twenty-one nurses indicated that they would use the leaflet and communication aid. Twenty-one nurses commented on intervention facilitators and barriers. More specific facilitators included their shared perception that "handing out the leaflet to patients was not problematic" and that the leaflet was seen as "applicable in many patient situations." Their comments indicated two particularly prominent barriers to conducting the intervention in clinical practice: 1) "finding the time for the implementation in the daily clinical routine and workload" and 2) "environmental factors like a noisy and busy atmosphere on the ward." Conclusions: This study provides insights into a patient involvement intervention featuring a structured nurse-patient discussion about fall risks. The accompanying information leaflet and communication guide require adaptations to facilitate sustainable implementation into the hospital's fall prevention program, but proved useful.